Ceratinadin G, a new psammaplysin derivative possessing a cyano group from a sponge of the genus Pseudoceratina - Shin-ichiro Kurimoto; Kouta Inoue; Taito Ohno; Takaaki Kubota (Beilstein Journal of Organic Chemistry)
A new psammaplysin derivative, ceratinadin G (1), was obtained from the Okinawan marine sponge Pseudoceratina sp., and the gross structure was clarified through spectroscopic and spectrometric analyses. The absolute configuration of compound 1 was established by comparing its NMR and ECD data with those of the known psammaplysin derivative, psammaplysin F (2). Ceratinadin G (1) is a rare nitrile containing a cyano group as aminoacetonitrile, and is the first psammaplysin derivative possessing a cyano group. In vitro assays indicated that compound 1 displayed moderate cytotoxicity against L1210 murine leukemia cells and KB epidermoid carcinoma cells.